Adaptive synchronization for complex networks with probabilistic time-varying delays. Issue 18 (December 2016) - Cheng, Ranran; Peng, Mingshu
Abstract: This paper addresses adaptive synchronization problem for complex networks with probabilistic time-varying delays. Using delay partitioning method and integral inequalities, combining with reciprocal convex combination approach technique, some delay-dependent synchronization stability criteria are derived. Finally, two numerical examples including Watts–Strogatz random complex networks and regular networks are provided to illustrate the importance of our theoretical analysis.